Characteristics of the Activity-Affect Association in Inactive People: An Ambulatory Assessment Study in Daily Life - Von Haaren, Birte; Loeffler, Simone N.; Haertel, Sascha; Anastasopoulou, Panagiota; Stumpp, Juergen; Hey, Stefan; Boes, Klaus (Frontiers in Psychology, 2013)
Acute and regular exercise as well as physical activity is related to wellbeing and positive affect. Recent studies have shown that even daily, unstructured physical activities increase positive affect. However, the attempt to achieve adherence to physical activity or exercise in inactive people through public health interventions has often been unsuccessful. Most studies analyzing the activity-affect association in daily life, did not report participants´ habitual activity behavior. Thus, samples included active and inactive people, but they did not necessarily exhibit the same affective reactions to physical activity in daily life. Therefore the present study investigated whether the association between physical activity and subsequent affective state in daily life can also be observed in inactive individuals. We conducted a pilot study with 29 inactive university students (mean age 21.3 yrs ± 1.7) using the method of ambulatory assessment. Affect was assessed via electronic diary and physical activity was measured with accelerometers. Participants had to rate affect every two hours on a six item bipolar scale reflecting the three basic mood dimensions energetic arousal, valence and calmness. We calculated activity intensity level (mean Metabolic Equivalent (MET) value) and the amount of time spent in light activity over the last 15 minutes before every diary prompt and conducted within-subject correlations. We did not find significant associations between activity intensity and the three mood dimensions. Due to the high variability in within-subject correlations we conclude that not all inactive people show the same affective reactions to physical activity in daily life. Analyzing the physical activity-affect association of inactive people was difficult due to little variance and distribution of the assessed variables. Interactive assessment and randomized controlled trials might help solving these problems. Future studies should examine characteristics of affect